Ferric Carboxymaltose in the Treatment of Iron-Deficiency Anaemia in Paediatric Patients with Anastomotic Ulcers - Chiara Udina; Maria Andrea Lanzetta; Fulvio Celsi; Egidio Barbi; Giulia Gortani; Matteo Bramuzzo; Grazia Di Leo (MDPI AG, 2022)
Objectives: The aim of this paper is to describe a case series of paediatric patients affected by anastomotic ulcers (AU), a late complication of bowel resection in infancy, focusing on the treatment of iron-deficiency anaemia (IDA) with ferric carboxymaltose (FC). Methods: Patients with a diagnosis of AU, treated at the Paediatric Department of the Institute for Maternal and Child Health IRCCS "Burlo Garofolo" from February 2012 to December 2020 were included. Haemoglobin (Hb) values, IDA related symptoms, the need for blood transfusions, for oral or intravenous (iv) iron supplementation and for surgical resections were compared before and after treatment with FC. Adverse effects of FC were recorded. Results: Ten patients with an established diagnosis of AU were identified; eight (8 out of 10) received at least one administration of FC. Lower and higher Hb values increased significantly after treatment (4.9 g/dL vs. 8.2 g/dL, p = 0.0003; 9.9 g/dL vs. 13.5 g/dL, p = 0.0008 respectively), with a significant reduction of the need for blood transfusions (p = 0.0051) and for oral and iv iron supplementation. While receiving standard therapies, seven patients (7 out of 8) complained of asthenia; this symptom resolved in all cases after FC administration. Before FC treatment, two patients (2 out of 8) required surgical resection of AU, with a recurrence of anaemia after a few weeks; after at least one FC infusion, no children needed further bowel resection for IDA. FC caused mild asymptomatic hypophosphatemia in one case. Conclusion: FC appears to be effective and safe in the paediatric population for the treatment of IDA resulting from AU.